2010
DOI: 10.1074/jbc.m109.089748
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Pattern of Mature Dimeric Leukocyte and Recombinant Monomeric Myeloperoxidase

Abstract: The involvement of myeloperoxidase (MPO) in various inflammatory conditions has been the scope of many recent studies. Besides its well studied catalytic activity, the role of its overall structure and glycosylation pattern in biological function is barely known. Here, the N-glycan composition of native dimeric human MPO purified from neutrophils and of monomeric MPO recombinantly expressed in Chinese hamster ovary cells has been investigated. Analyses showed the presence of five N-glycans at positions 323, 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 34 publications
7
46
0
Order By: Relevance
“…As a peroxidase, the most vital physiological function of MPO is determined by its enzymatic activity, to catalyze the production of hypochlorous acid and reactive oxygen species, and to participate in the antimicrobial mechanism in circulation and at sites of inflammation . A recent study indicated glycosylation as being critical to the enzymatic activity of MPO; our results are consistent in this respect. We further investigated the effect of each glycan on the oxidation function of MPO.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As a peroxidase, the most vital physiological function of MPO is determined by its enzymatic activity, to catalyze the production of hypochlorous acid and reactive oxygen species, and to participate in the antimicrobial mechanism in circulation and at sites of inflammation . A recent study indicated glycosylation as being critical to the enzymatic activity of MPO; our results are consistent in this respect. We further investigated the effect of each glycan on the oxidation function of MPO.…”
Section: Discussionsupporting
confidence: 89%
“…The mature MPO protein consists of two light and two heavy polypeptide chains with each heavy chain binding to prosthetic heme group . Mass spectrometry has demonstrated the presence of five N‐linked glycosylation sites in each MPO heavy chain, which are occupied by either complex or high mannose glycan structures . The overall structures of MPO glycan and the biological effects of glycosylation patterns on MPO function are not well characterized.…”
mentioning
confidence: 99%
“…MPO also contains a calcium binding site contributing to the stabilization of the structure. N-glycans play a key role in protein synthesis and also in enzymatic activity as recently shown by our experiments [52]. Furthermore, MPO is a highly cationic protein with a pI ≈ 11 enabling its binding to electronegative surfaces such as endothelial wall, lipoprotein, or proteoglycans [53, 54].…”
Section: Myeloperoxidase and Mpo/h2o2/halide Systemmentioning
confidence: 82%
“…This matches with five N-glycans in mature homodimeric MPO and pro-MPO produced in CHO cell lines (21). Monomeric bovine lactoperoxidase has four N-glycosylation sites (38).…”
Section: Journal Of Biological Chemistry 10885mentioning
confidence: 96%
“…For N-glycan site occupancy, a rapid resolution liquid chromatographic system (1200 series) coupled to a quadrupole/ time-of-flight equipped with an electrospray ionization source (ESI-QTOF 6520 series) mass spectrometer (Agilent Technologies, Palo Alto, CA) was used for analysis of the aforementioned protein digests (21). As PNGase F removes glycans and performs deamination of asparagine (Asn 3 Asp), the glycosylation occupancy was calculated by measuring the ratio between the area under the curve of the native peptide and its deaminated form.…”
Section: Methodsmentioning
confidence: 99%